2016
DOI: 10.1186/s40834-016-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

The yield of endometrial aspiration in women with various risk factors and bleeding abnormalities

Abstract: BackgroundEven in the face of a substantial increase in the numbers of endometrial cancer cases and in the numbers of women who have risk factors, there is no clear agreement about the indications for assessing the endometria of women with abnormal bleeding or about the tools to use in that assessment. This study sought to determine in a group of high risk women with abnormal uterine bleeding, the probability that an outpatient endometrial aspiration would identify significant pathology.MethodsRetrospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…[ 9 ] and Kaur et al . [ 10 ] in India as well as in western countries [ 11 12 ] where endometrial aspiration was compared with traditional methods for adequacy of samples.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] and Kaur et al . [ 10 ] in India as well as in western countries [ 11 12 ] where endometrial aspiration was compared with traditional methods for adequacy of samples.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of EC in younger patients is suggested to be lower and can easily be misdiagnosed as abnormal uterine bleeding, whereas older patients are more likely to be diagnosed at an early stage [ 8 ]. Nelson et al [ 9 ] found no association between increasing age and the prevalence of endometrial hyperplasia, which was more common in women aged < 40 years than in those aged 40–50 years. Clinically, patients younger than 45 years were defined as having early onset EC.…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial carcinoma, which is the most frequent gynecologic malignancy in the United States, often presents with abnormal uterine bleeding. As a result, endometrial sampling is part of the diagnostic evaluation for AUB in women with risk factors, including obesity, null parity, significant family history and postmenopausal bleeding [1][2][3]. The specific indication for performing endometrial biopsy, however, varies amongst expert panels.…”
mentioning
confidence: 99%